2019
DOI: 10.1155/2019/4828563
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Oxaliplatin-Induced Neuropathic Pain Symptoms in Each Cycle and Its Implications on the Management of Colorectal Cancer Patients: A Retrospective Study in South Western Sydney Local Health District Hospitals, Sydney, Australia

Abstract: Oxaliplatin-induced neuropathic pain limits treatment compliance. However, the variability of neuropathic pain symptoms in each cycle for individual patients and the impacts on treatment compliance remain untested. Data from 322 adult patients who received oxaliplatin-based chemotherapy were extracted based on pattern of chemotherapy, adverse events, and patient survival. Cox regression and survival analyses were employed. Seventy-eight percent of patients developed neuropathic pain that oscillated between a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…The prevalence of neuropathic pain (20%) in this study is similar to the French CRC survivors 5 years after FOLFOX chemotherapy of 15.4% (Selvy et al, 2020), but higher than a study that reported 9% in long‐term CRC survivors (Bonhof et al, 2020) and lower than Australian individuals with cancer receiving oxaliplatin‐based chemotherapy at 78% (Gebremedhn et al, 2019). The difference may be due to Bonhof et al (2020) using the European Organization of Research and Treatment Cancer Quality of Life Questionnaire‐CIPN 20‐item scale (EORTC QLQ‐CIPN 20) for neuropathic pain measures which are not as specific for neuropathic pain as IDQ utilized in our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The prevalence of neuropathic pain (20%) in this study is similar to the French CRC survivors 5 years after FOLFOX chemotherapy of 15.4% (Selvy et al, 2020), but higher than a study that reported 9% in long‐term CRC survivors (Bonhof et al, 2020) and lower than Australian individuals with cancer receiving oxaliplatin‐based chemotherapy at 78% (Gebremedhn et al, 2019). The difference may be due to Bonhof et al (2020) using the European Organization of Research and Treatment Cancer Quality of Life Questionnaire‐CIPN 20‐item scale (EORTC QLQ‐CIPN 20) for neuropathic pain measures which are not as specific for neuropathic pain as IDQ utilized in our study.…”
Section: Discussionsupporting
confidence: 78%
“…The difference may be due to Bonhof et al (2020) using the European Organization of Research and Treatment Cancer Quality of Life Questionnaire‐CIPN 20‐item scale (EORTC QLQ‐CIPN 20) for neuropathic pain measures which are not as specific for neuropathic pain as IDQ utilized in our study. The Australian study asked only about the frequency and magnitude of acute and chronic neuropathies in cancer survivors who received oxaliplatin‐based chemotherapy (Gebremedhn et al, 2019), while our study did not specify acute from chronic neuropathic pain and focused solely on advanced CRC individuals. The prevalence rate of neuropathic pain in the literature was highly inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative sensory testing (QST) examines subjective sensory function by measuring the abnormal detection and pain thresholds to several sensory modalities. The usefulness of these non-invasive psychophysical measurements in the clinic setting for detecting subclinical neurologic changes early on to identify patients that will experience OXAIPN has been largely explored [ 12 , 20 , 20 , 42 , 51 , 53 , 54 , 56 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Neurophysiological and Device-dependent Predictorsmentioning
confidence: 99%
“…A referência à dose cumulativa (m²) é a mais expressiva quantitativamente e emerge em treze estudos dessa revisão 22,24,25,27,29,31,33,[35][36][37][42][43][44] . Outros dois referem-se ao início das manifestações de Neuropatia, a partir de ciclos específicos, em associação com determinado somatório, média ou mediana de dose cumulativa 22,25 . Apenas Hsu, et al 24 estudo a menciona como fator preditivo, sem, contudo, delimitar valor numérico.…”
Section: Preferred Reporting Items For Systematic Reviews Andunclassified